Three Varieties of Africa's Industrial Future - Wim Naudé (Institute of Labor Economics (IZA), 2019)
This paper shows that African economies have generally not de-industrialized, that manufacturing growth is very possible, and moreover that the contribution of manufacturing in Africa has been underestimated. As far as the future is concerned, African countries will in differing degrees experience three varieties of industrialization, all influenced by new and emerging technologies. In one variety, labelled "acquiring traditional manufacturing capabilities" technological change is too fast and complex for some countries to immediately benefit, requiring an estimated 15-year window to put the complementary investments and business ecosystems in place, while promoting old-fashioned labor-intensive manufacturing. In a second variety, technological innovation is changing the nature of manufacturing and is turning services into the main sector for structural transformation. This variety is labelled "fostering sectors with the characteristics of manufacturing" to denote that services now perform functions previously expected from manufacturing. A third variety of future industrialization is labelled "resurgent entrepreneurship-lead industrialization" denoting that some African countries will take part in new and advanced types of manufacturing, through indigenous entrepreneurs starting high-technology firms. This third variety is elaborated with reference to recent examples. The paper concludes with broad suggestions for industrial policies that are consistent with these varieties of industrialization.
Keywords: O47; O33; J24; E21; E25; 330; technology; entrepreneurship; manufacturing; industrial policy; Africa